Hubungan Dukungan Keluarga Dengan Kepatuhan Pasien Dalam Perawatan Luka Kaki Diabetik di RSUD Anuntaloko Parigi - Maria Doki, Adisty; Siti Yartin; Sabir (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
One of the main determinants of patient compliance with diabetic foot wound management is family support. Amputation and other more severe consequences can occur due to non-compliance. The purpose of this study was to find out how family support and patient compliance with diabetic foot wound care at Anuntaloko Parigi Hospital are interrelated. Cross-sectional methodology and quantitative design were used in the investigation. Based on the established inclusion and exclusion criteria, a purposive selection approach was used to select a sample of 51 respondents. The Hensarling Diabetes Family Support Scale (HDFSS) and the Morisky Medication Adherence Scale (MMAS-8) were used as research instruments. Using the Chi-Square test, data analysis was performed univariately and bivariately. The majority of respondents reported strong compliance (64.7%) and significant family support (68.6%), according to statistics. Family support and patient compliance with diabetic foot wound care were significantly correlated, according to the findings of the statistical test (p = 0.001). Conclusion: There is a significant relationship between family support and patient compliance in diabetic foot wound care at Anuntaloko Parigi Hospital. Increased family involvement and support can encourage patients to be more compliant in undergoing consistent and effective wound care.